Coexistent Non–Small Cell Carcinoma and Small Cell Carcinoma in a Patient Presenting with Hyponatremia - Mitchell D. Ross; Sreeja Biswas Roy; Pradnya D. Patil; Jasmine L. Huang; Nitika Thawani; Ralph Drosten; Tanmay S. Panchabhai (Case Reports in Pulmonology)
Despite recent advances in screening methods, lung cancer remains the leading cause of cancer-related deaths worldwide. By the time lung cancer becomes symptomatic and patients seek treatment, it is often too advanced for curative measures. Low-dose computed tomography (CT) screening has been shown to reduce mortality in patients at high risk of lung cancer. We present a 66-year-old man with a 50-pack-year smoking history who had a right upper lobe (RUL) pulmonary nodule and left lower lobe (LLL) consolidation on a screening CT. He reported a weight loss of 45 pounds over 3 months, had recently been hospitalized for hyponatremia, and was notably cachectic. A CT of the chest showed a stable LLL mass-like consolidation and a 9×21 mm subsolid lesion in the RUL. Navigational bronchoscopy biopsy of the RUL lesion revealed squamous non–small cell lung cancer (NSCLC). Endobronchial ultrasound-guided transbronchial needle aspiration of the LLL lesion revealed small cell lung cancer (SCLC). The final diagnosis was a right-sided Stage I NSCLC (squamous) and a left-sided limited SCLC. The RUL NSCLC was treated with stereotactic radiation; the LLL SCLC was treated with concurrent chemotherapy and radiation. In patients with multiple lung nodules, a diagnosis of synchronous multiple primary lung cancers (MPLCs) is crucial, as inadvertent upstaging of patients with MPLC (to T3 and/or T4 tumors) can lead to erroneous staging, inaccurate prognosis, and improper treatment. Recent advances in the diagnosis of small pulmonary nodules via navigational bronchoscopy and management of these lesions dramatically affect a patient’s overall prognosis.